The Efficacy of 0.03% Dermatological Tacrolimus Ointment for Refractory Vernal Keratoconjunctivitis. - Imtiaz, Hafiza Sadia; Qayyum, Irfan; Iqbal, Usama; Ali, Farhan; Sharjeel, Muhammad (Pakistan Journal of Ophthalmology, 2020)
Purpose: To determine the efficacy of 0.03% dermatological tacrolimus ointment in patients with refractory vernal keratoconjunctivitis Study Design: Quasi-experimental study Study Place and Duration: Eye Department, DHQ-Teaching Hospital, Gujranwala, Pakistan from April 2018 to March 2019 Material and Methods: After approval from hospital ethical committee and obtaining written informed consent from each patient/guardian, patients of either gender between 4-16 years of age with VKC not responding to conventional treatment for more than 8 weeks or having steroid-induced complications were included in this study. Dermatological tacrolimus ointment 0.03% started to be placed in inferior fornix in BD frequency along with topical lubricants. Patients were followed up on a regular schedule. Individual symptoms score was assessed from the questionnaire and signs score from observer’s clinical assessment. Data were analyzed using SPSS v23.0. P-value <0.05 was considered as statistically significant. Results: 40 eyes of 20 patients were included in this study. Out of which 4(20%) were female and 16 were male (80%). Mean baseline score for clinical symptoms was 6.65±1.81 that reduced to 1.65±0.81 after 12 weeks treatment course of tacrolimus with a significant p-value of 0.006 (p<0.05). Mean baseline score for clinical signs was 5.9±1.59 that improved to 1.80±0.83 after 12 weeks treatment course with a statistically significant p-value of 0.003 (p<0.05). Conclusions: In conclusion, topical tacrolimus dermatological ointment 0.03% is highly effective in refractory VKC and can be safely used as an alternative in VKC patients who are steroid-responders.